Pembelajaran Statistik Melalui Model Pembelajaran Kooperatif Tipe Snowball Throwing untuk Meningkatkan Hasil Belajar di Kelas VII SMP Negeri 1 Singosari - Dewi Asmarani (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2017)
Cooperative learning and problem submission is one of the learning models that can be developed and implemented to solving the problem of low activity and learning achievement. One method of cooperative learning can be used to enable students to said their problem is snowball throwing method. This study used a qualitative approach in this case is classroom action research, which consists of two cycles. The result showed that the snowball throwing is proven to help improve learning outcomes of students of class VII-E SMP Negeri 1 Singosari in Statistics. This can be shown on the score of the average value obtained from the initial data, the first cycle and the second cycle (71, 75, and 80) and the thoroughness of classical learning was 83.3%. Therefore, it is recommended to teachers of mathematics to use Snowball Throwing.